Enhancing Numerical Intelligence through Higher Order Thinking Skills in Learning Management - Alhakiki, Abdika; Miaz, Yalvema (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the application of Higher Order Thinking Skills in learning management to improve students' numerical intelligence in public elementary schools in Tebo District. This study uses a qualitative approach to the type of case study. The data in this study were obtained from interviews, observation and documentation. Data analysis was carried out using a qualitative approach involving organizing, coding, searching for themes, and developing patterns of findings. The results of the study show that there are three steps in learning management regarding HOTS-based learning management in improving students' numerical intelligence, namely; 1) Planning of learning whose indicators are in the form of analysis components, 2) Implementation of learning whose indicators are in the form of evaluations, and 3) Controlling, whose indicators are in the form of creating components. The results of this study provide practical insights for educators in optimizing the application of HOTS in classroom learning management to improve students' numerical intelligence. This study offers a greater comprehension of how the application of HOTS might be incorporated within learning management. This enhances our knowledge of the value of HOTS in raising students' numerical intelligence, which adds to the body of academic literature.